A Community-Based Conservation Initiative for Wolves in the Ladakh Trans-Himalaya, India - Sonam, Karma; Dorjay, Rigzen; Khanyari, Munib; Bijoor, Ajay; Lobzang, Sherab; Sharma, Manvi; Suresh, Shruti; Mishra, Charudutt; Suryawanshi, Kulbhushansingh R. (Frontiers in Ecology and Evolution, 2022)
We describe a pilot community-based conservation initiative for wolves Canis lupus that involves (i) voluntary deactivation of traditional trapping pits called Shandong, (ii) commitment to wildlife conservation by the local community, and (iii) collaborative construction and consecration of a Stupa (Buddhist shrine) in the vicinity of the Shandong as a symbol of conservation and repentance for past hunting. People and wolves have a complex relationship, in part shaped by predation on livestock, which can have severe impacts on livelihoods in pastoral societies. Consequently, wolf conservation often evokes strong and polarizing reactions. To control wolf populations, livestock herders across the Trans- Himalayan and Tibetan regions use different types of traps. Shandong is a relatively large, widely used traditional trapping pit with inverted funnel-shaped stone walls, usually built near villages or herder camps. Typically, a live domestic animal is placed in the pit to attract the wolves. Once the wolves jump into the pit, the funnel-shaped walls prevent them from escaping, and trapped wolves are usually stoned to death. In an extensive survey covering over 25,000 sq. km, we enumerated 94 Shandong in 58 of the 64 surveyed villages in Ladakh between June 2019 – March 2020. Thirty of these had been used to kill wolves within the past 10 years, while 7 had been destroyed. Shandong that were not in use were of poorer condition. Since 2017, we have worked with community members, local monks, and the region’s religious leaders to support the neutralization of the Shandong while preserving their structure, and assisted the communities to build stupas and to consecrate them. Our pilot efforts with three communities appear to generate pride locally and hold promise for promoting wolf conservation in Ladakh and in large parts of Trans-Himalayan and Tibetan regions that share similar cultural settings.